2020
DOI: 10.1103/physrevlett.125.026802
|View full text |Cite
|
Sign up to set email alerts
|

Proximity-Induced Odd-Frequency Superconductivity in a Topological Insulator

Abstract: At an interface between a topological insulator (TI) and a conventional superconductor (SC), superconductivity has been predicted to change dramatically and exhibit novel correlations. In particular, the induced superconductivity by an s-wave SC in a TI can develop an order parameter with a p-wave component. Here we present experimental evidence for an unexpected proximity-induced novel superconducting state in a thin layer of the prototypical TI, Bi 2 Se 3 proximity coupled to Nb. From depthresolved magnetic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 44 publications
2
28
0
Order By: Relevance
“…Finally, the observation of the paramagnetic shift in the SC state of Nb 0.25 Bi 2 Se 3 , instead of the expected diamagnetic shift imposed by the SC state, deserves some attention. In general, the paramagnetic shift can have few possible causes: field-induced magnetism [60,61], vortex disorder [62], oddfrequency superconducting state [63], and by the suppression of the negative Knight shift below T c due to singlet pairing. Considering the absence of any trace of magnetism in Nb 0.25 Bi 2 Se 3 and the symmetric line shape from TF-μSR, magnetism and disorder effects can be excluded as being the origin of the observed paramagnetic shift.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the observation of the paramagnetic shift in the SC state of Nb 0.25 Bi 2 Se 3 , instead of the expected diamagnetic shift imposed by the SC state, deserves some attention. In general, the paramagnetic shift can have few possible causes: field-induced magnetism [60,61], vortex disorder [62], oddfrequency superconducting state [63], and by the suppression of the negative Knight shift below T c due to singlet pairing. Considering the absence of any trace of magnetism in Nb 0.25 Bi 2 Se 3 and the symmetric line shape from TF-μSR, magnetism and disorder effects can be excluded as being the origin of the observed paramagnetic shift.…”
Section: Discussionmentioning
confidence: 99%
“…The physics of topological superconductors (TSCs) has attracted considerable attention [1][2][3][4][5][6][7][8]. However, despite tremendous research activity, only a few materials with the potential to act as bulk topological superconductors, including Sr 2 RuO 4 [9], the Weyl semimetal T d -MoTe 2 [10], Cu/Sr/Nbdoped Bi 2 Se 3 [11][12][13][14][15][16], and PdTe 2 [17], have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, the detection of odd-ω pairing has remained a theoretical chimera and only very recently has its experimental realization apparently been confirmed. One recent study has reported odd-ω superconductivity at the interface of a topological insulator with a conventional superconductor [29]. In another recent development, which builds upon earlier theoretical work [30,31], the presence of an odd-ω component in scanning tunneling spectroscopy (STS) has finally been reported in a system of a magnetic impurity in contact with a conventional superconductor [32].…”
Section: Introductionmentioning
confidence: 99%